Effect of land use change, cropping systems and soil type on earthworm cast production in West and Central Africa - Hauser, S.; Norgrove, L.; Asawalam, D.; Schulz, S. (Elsevier, 2012)
Data on earthworm surface cast deposition in undisturbed, cropped and recovering sites from West and Central Africa were compiled to assess the effects of land use system (LUS) change and if casting can be used to indicate soil quality. Annual cast deposition in undisturbed systems was significantly higher on Alfisols (49,000 kg ha 1) than on Ultisols (25,000 kg ha 1). Vegetation clearance had significant detrimental effects on earthworm activity. With an increasing length of continuous cropping, cast deposition declined. In young fallows, cast production exceeded levels attained in previously un-cropped controls on Alfisols, yet, on Ultisols, it depended on the previous LUS and length of the previous cropping phase. Recovery was highest after agrisilviculture and after clearing bush fallow. After forest clearance, burning and one year cropping, cast deposition did not recover within three years. On Alfisols, cast production was higher under planted tree fallow and natural fallow than under herbaceous fallow. On Ultisols, fallow type had no effect. Earthworm surface cast production contributes to soil quality. However, its suitability as an indicator of soil quality is limited to rough assessments as it is dependent upon earthworm species composition, vegetation management and soil type, with more drastic changes on the poorer Ultisols than the morefertile Alfisols.